2011
DOI: 10.1186/1471-2377-11-44
|View full text |Cite
|
Sign up to set email alerts
|

Aggravated stuttering following subthalamic deep brain stimulation in Parkinson's disease - two cases

Abstract: Stuttering is a speech disorder with disruption of verbal fluency which is occasionally present in patients with Parkinson's disease (PD). Long-term medical management of PD is frequently complicated by fluctuating motor functions and dyskinesias. High-frequency deep brain stimulation (DBS) of the subthalamic nucleus (STN) is an effective treatment of motor fluctuations and is the most common surgical procedure in PD. Here we report the re-occurrence and aggravation of stuttering following STN-DBS in two male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Depression and mania also seem to have the same relationship with dopamine concentration and are often associated with slow and rapid speech, respectively [17]. It was also noted that one of the cases in the study by Toft and Dietrichs [12] was a man with emerging stuttering caused by DBS-STN. He had no history of stuttering but reported a history of an abnormally fast speech since childhood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depression and mania also seem to have the same relationship with dopamine concentration and are often associated with slow and rapid speech, respectively [17]. It was also noted that one of the cases in the study by Toft and Dietrichs [12] was a man with emerging stuttering caused by DBS-STN. He had no history of stuttering but reported a history of an abnormally fast speech since childhood.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, presurgical dysarthria can be aggravated by DBS and dysarthria may emerge as a side effect. Re-occurring and aggravated stuttering has been reported in 2 cases of DBS-STN where speech fluency improved considerably when the stimulator was turned off [10,11,12]. However, unilateral DBS-STN to the language-dominant hemisphere has been reported to improve acquired stuttering associated with PD in a case study [13], and bilateral DBS-STN has recently been reported to improve developmental stuttering in another case study [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding fluency, a study of two cases evaluated the speech fluency in the DBS at the 'on' and 'off' moments and concluded that the speech fluency improved in both patients when the stimulator was turned off, suggesting that DBS may negatively affect speech fluency (20) . Articulation is directly affected by the PD motor symptoms and, therefore, a post-DBS improvement is expected, even though other variables may interfere in these results, such as disease progression and use of dopaminergic medication.…”
Section: Discussionmentioning
confidence: 99%
“…In DBS for parkinsonism, immediately presenting side effects include paresthesia (Roggendorf et al 2008), eyelid apraxia (Tommasi et al 2012), stuttering (Toft and Dietrichs 2011), and many others. The other category includes side effects that are often psychological in presentation and may take weeks or months to properly diagnose.…”
Section: Clinical Deep Brain Stimulation Therapymentioning
confidence: 99%